Lifestyle and psychosocial associations with cognition at the cusp of midlife using twins and siblings - Anqing Zheng; Naomi P. Friedman; Daniel E. Gustavson; Robin P. Corley; Sally J. Wadsworth; Chandra A. Reynolds (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2024)
Abstract INTRODUCTION This study investigates the relationship between cognitive functioning and 59 modifiable and intrinsic factors at the cusp of midlife. METHODS We analyzed data from 1221 participants in the Colorado Adoption/Twin Study of Lifespan behavioral development and cognitive aging (CATSLife; Mage = 33.20, %Female = 52.74). We assessed the impact of 59 factors on cognitive functioning using regularized regression and co‐twin control models, controlling for earlier‐life cognitive functioning and gray matter volume. RESULTS Eight robust factors were identified, including education attainment, cognitive complexity, purpose‐in‐life, and smoking status. Twins reporting higher levels of cognitive complexity and purpose‐in‐life showed better cognitive performance than their cotwin, while smoking was negatively associated. Using meta‐analytically derived effect size threshold, we additionally identified that twins experiencing more financial difficulty tend to perform less well compared with their cotwin. DISCUSSION The findings highlight the early midlife link between cognitive functioning and lifestyle/psychological factors, beyond prior cognitive performance, brain status, genetic and familial confounders. Our results further highlight the potential of established adulthood as a crucial window for dementia prevention interventions targeting lifestyle and psychosocial factors. Highlights Cog complexity(+), purpose‐in‐life(+) were associated with cognition in early midlife. Smoking(−) was also associated with cognition in early midlife. Results were consistent controlling for genetic and environmental confounds. Association between EA and cognition might be mostly genetic and familial confounded.